Genetic analysis of a female patient with X-linked lymphoproliferative disease type 2: a case report - Yalin Sun; Shu Teng; Wen Li; Huaping Wang; Zhenghong Qi (Journal of Medical Case Reports)
Abstract Background X-linked lymphoproliferative syndrome type 2 is a relatively rare primary immunodeficiency disease caused by mutations in XIAP. X-linked lymphoproliferative syndrome type 2 typically occurs in male individuals, while female individuals are carriers of the pathogenic gene mutations. Furthermore, X-linked lymphoproliferative syndrome type 2 has a complex clinical phenotype. We aimed to explore the pathogenesis of X-linked lymphoproliferative syndrome type 2 through genetic testing of a family to provide a basis for clinical diagnosis. Case presentation The clinical data of a female patient with X-linked lymphoproliferative syndrome type 2 and her family were collected and analyzed. The patient was 2 years 1 months old and of Han Chinese descent. Methylation-sensitive restriction enzyme amplification and capillary electrophoresis were used to detect X chromosome inactivation in the family. A novel mutation, c.910G > T (guanine to thymine), was identified in XIAP in the patient and her brother, but was not detected in the patient’s parents. The proportion of chromosomal inactivation in the female children was 86%, which indicates a moderate inactivation shift and paternal inactivation shift. Conclusion Close attention should be paid to shifts in X-chromosome inactivation in female children. When a pathogenic gene variant is not detected in a mother with a normal phenotype, gonadal mosaicism cannot be ruled out, and prenatal genetic diagnosis should be performed in the next pregnancy.